Synthesis, Characterization, and Evaluation of a Novel Molecularly Imprinted Polymer (MIP) for Selective Quantification of Curcumin in Real Food Sample by UV-Vis Spectrophotometry - Espinoza-Torres, Sergio; López, Rosario; Sotomayor, Maria D. P. T. [UNESP]; Tuesta, Juan C.; Picasso, Gino; Khan, Sabir [UNESP] (MDPI, 2023)
Curcumin is the main colorant of the curcuma longa plant, a food with many benefits for human health. This work aims to synthesize a novel molecularly imprinted polymer (MIP) for the selective detection of curcumin in real samples obtained from the local market of Peru. MIPs were synthesized via bulk polymerization using curcumin, acrylamide, ethylene glycol dimethacrylate, ABCV, and acetonitrile. FTIR spectra showed equal spectra for MIP and NIP. N2 physisorption analysis presented a higher value BET surface for the MIP (28.5 m2 g−1) compared to the NIP (18.5 m2 g−1). The adsorption capacity of the MIP was evaluated using UV-vis spectrophotometry in the band around 430 nm. The adsorption kinetics found were of pseudo-second-order and a Qe value of 16.2 mg g−1. Furthermore, the adsorption process resembles the Freundlich adsorption model with a heterogeneity factor of less than 1 (0.61) and Kf greater for MIP (1.97). The selectivity test indicated that MIP is more selective for curcumin (Q = 13.20 mg g−1) than against interferents (Q = 2.19 mg g−1). The specific selectivity factor (S) obtained for the interferents was greater than 1 which indicates a good selectivity. Finally, the application of MIP in real samples using UV-vis spectrophotometry yielded a recovery value greater than 70%.
Keywords: adsorption; bulk polymerization; curcumin; MIP